2011
DOI: 10.1007/978-3-642-20525-5_28
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining Using Unguided Symbolic Regression on a Blast Furnace Dataset

Abstract: Abstract. In this paper a data mining approach for variable selection and knowledge extraction from datasets is presented. The approach is based on unguided symbolic regression (every variable present in the dataset is treated as the target variable in multiple regression runs) and a novel variable relevance metric for genetic programming. The relevance of each input variable is calculated and a model approximating the target variable is created. The genetic programming configurations with different target var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…One modeling approach for the analysis of complex systems are variable interaction networks [8] -directed graphs representing system variables as nodes and their impact on others as weighted edges. Primarily, variable interaction networks have been employed to gain a better understanding of the interdependencies within a modeled system [4]. In this work however, we utilize them to detect changing system behavior -so-called concept drifts [3] -online.…”
Section: Motivationmentioning
confidence: 99%
“…One modeling approach for the analysis of complex systems are variable interaction networks [8] -directed graphs representing system variables as nodes and their impact on others as weighted edges. Primarily, variable interaction networks have been employed to gain a better understanding of the interdependencies within a modeled system [4]. In this work however, we utilize them to detect changing system behavior -so-called concept drifts [3] -online.…”
Section: Motivationmentioning
confidence: 99%
“…According, to the authors [12] this paper revealed a data mining approach for variable selection and knowledge extraction from the dataset. The approach is based on unguided symbolic regression (every variable present in the dataset is treated as the target variable in multiple regression runs) and a novel variable relevance metric for genetic programming.…”
Section: Reviewmentioning
confidence: 99%
“…Kommenda et al (2011) used an unguided symbolic regression approach for variable selection and knowledge extraction from BF dataset. In this work, Genetic Programming (GP) (Koza 1992) was executed multiple times for reducing the stochastic effects and for identifying important variables through a variable interaction network.…”
Section: Figure 2: a Diagram Of The Blast Furnace In The Iron-making mentioning
confidence: 99%